Terminological definition of the category “Interpretation in international law”: historical transformations of the definitions and new approaches - Карвацька, Світлана Богданівна (Miscellanea Historico-Iuridica, 2020)
The problem of transformations of the definition “Interpretation in international law” is analyzed in the article. Particularly acute and ambiguous is the question of differentiation of the concepts “interpretation” and “explanation”, which are used in the domestic theory of international law. In Western literature, mostly, the term “interpretation” is used (from the Latin interpretatio). It is determined that two concepts, which Ukrainian lawyers often see as identical or synonymous, the national experts in international law often consider to be rather problematic. From the point of view of the Ukrainian legislation, the concept of “interpretation” is legal, and lawyers use in legal practice and theory such terms as interpretation of the law, interpretation of the legal act, legal interpretation, interpretation of the rules of law, interpretation of the norms of international law. The author notes that this not only does not introduce categorical unambiguity and clarity, but rather complicates the integration of Ukrainian legal science and the science of the theory of international law in the European scientific system.
Keywords: interpretation in international law, correlation of interpretation and hermeneutics, an international treaty